Efektivitas Program Pembangunan PSP terhadap Etos Kerja Petani Desa Ngadisuko, Kabupaten Trenggalek, Jawa Timur - Iklil Siffana; Ugik Romadi; Gunawan Gunawan (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluhan Pembangunan Indonesia), 2021)
This research focused on the influence of PSP Development Program’s (Farming Infrasturcture) toward farmer’s working ethos in Ngadisuko village from February to July 2020. This research was focused to examinethe effectiveness of the Farming Machineries Program’s and Subdisized Fertilizer Program’s toward farmer’s working ethos. Primary method used in this research are closed quetionaire survey with Likert scale using sample of 90 farmers tested dan regression model test based on Ordinary Least Square method. The result showed that there is significant degree of influence; simultaneously between farming machineries and subsidized fertilizer and effectivity toward farmer’s working ethos. However partially inter-variable test showed there is no significant degree of influence toward working ethos and has low influence for 22,5%. This is due to many problems in the implementation of programs aren’t perfect and must be immediately fixed.